Geologia e geocronologia de zircões detríticos da Região de Serro, Serra do Espinhaço Meridional, Minas Gerais, Brasil - Vitor Diniz Silveira (2016)
This work describes the results of stratigraphic, tectonic and geochronological studies in Serro, MG. The metasediments were divided into four lithostratigraphic units: Unit I consists of rudaceos sediments, metaconglomerate and quartzite; Unit II is composed of quartzite with metaconglomerate and phyllite; Unit III corresponds to banded iron formation; and Unit IV consists of quartzite. These units are correlated with the formations of the Serra São José Group reported by Rolim et al., (2016) to the south, with maximum deposition ages in 1666 ± 32 Ma, and can be considered as a lateral continuation of these layers towards north.The basin deposition evolved at the end of the Paleoproterozoic, Statherian period, defined by the younger ages of detrital zircons found at the base, with age 1683 ± 30 Ma, and at the top with age 1596 ± 19 Ma.The stratigraphic stacking of basal units, together with the maximum age of sedimentation and similar distributions of populations of zircons in the histograms, propose the correlation of these units with the São João da Chapada Formation outcropping west in the southern Espinhaço Range.The results of geochronological and stratigraphic studies allow new interpretation to the banded iron formation of Serro, revealing that this unit is associated of Statherian rocks that constitute the Espinhaço Supergroup rift sequences.